Implementasi Metode Collaborative Learning untuk Meningkatkan Keterampilan Interpersonal Mahasiswa - Sekarinasih, Anggitiyas (QUALITY, 2022)
The purpose of this study was to see the impact of implementing collaborative learning learning methods to improve interpersonal skills of PGMI IAIN Purwokerto students. This research is included in the type of classroom action research (CAR) by adopting Mc Kernan's theory which uses seven stages consisting of problem description, needs assessment, idea hypothesis, action plan, plan implementation, evaluation and decision making which is divided into three major activities namely (1) planning, (2) plan implementation, and (3) evaluation and decision making. The data collection techniques used were observation, Focus Group Discussion (FGD), interviews and questionnaires. The results of this study were selected two learning strategies that fall into the category of collaborative learning learning methods, namely the group resume strategy and study group. The application of the group resume strategy can improve students' interpersonal skills in the interpersonal relationship section, but it is not optimal for improving relationships between groups. As for the study group strategy, it is proven to improve students' interpersonal skills both in the relationship between individuals and individuals, individuals with groups and relationships between groups and groups.